Muslim pilgrimage in Europe - Flaskerud, Ingvild; Natvig, Richard Johan (Routledge studies in pilgrimage, religious travel, and tourism, 2018)
In spite of Islam's long history in Europe and the growing number of Muslims resident in Europe, little research exists on Muslim pilgrimage in Europe. This collection of eleven chapters is the first systematic attempt to fill this lacuna in an emerging research field. Placing the pilgrims' practices and experiences centre stage, scholars from history, anthropology, religious studies, sociology, and art history examine historical and contemporary hajj and non-hajj pilgrimage to sites outside and within Europe. Sources include online travelogues, ethnographic data, biographic information, and material and performative culture. The interlocutors are European-born Muslims, converts to Islam, and Muslim migrants to Europe, in addition to people who identify themselves with other faiths. Most interlocutors reside in Albania, Bosnia-Hercegovina, Italy, France, the Netherlands, Great Britain, and Norway. This book identifies four courses of developments: Muslims resident in Europe continue to travel to Mecca and Medina, and to visit shrine sites located elsewhere in the Middle East and North Africa. Secondly, there is a revival of pilgrimage to old pilgrimage sites in South-eastern Europe. Thirdly, new Muslim pilgrimage sites and practices are being established in Western Europe. Fourthly, Muslims visit long-established Christian pilgrimage sites in Europe. These practices point to processes of continuity, revitalization, and innovation in the practice of Muslim pilgrimage in Europe. Linked to changing sectarian, political, and economic circumstances, pilgrimage sites are dynamic places of intra-religious as well as inter-religious conflict and collaboration, while pilgrimage experiences in multiple ways also transform the individual and affect the home-community